2011
DOI: 10.1152/ajplung.00465.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory domain phosphorylation to distinguish the mechanistic basis underlying acute CFTR modulators

Abstract: Pyle LC, Ehrhardt A, Mitchell LH, Fan L, Ren A, Naren AP, Li Y, Clancy JP, Bolger GB, Sorscher EJ, Rowe SM. Regulatory domain phosphorylation to distinguish the mechanistic basis underlying acute CFTR modulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…Furthermore, in line with previous findings demonstrating that pharmacological molecules (correctors and potentiators) might increase the susceptibility of the R-domain of F508del CFTR to be phosphorylated (Pyle et al, 2011), we found that both correctors increase both the cAMP and the activated PKA compartmentalization in the sub-plasma-membrane region, allowing the consequent rescue of F508del-CFTR-dependent chloride efflux (Fig. 3).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in line with previous findings demonstrating that pharmacological molecules (correctors and potentiators) might increase the susceptibility of the R-domain of F508del CFTR to be phosphorylated (Pyle et al, 2011), we found that both correctors increase both the cAMP and the activated PKA compartmentalization in the sub-plasma-membrane region, allowing the consequent rescue of F508del-CFTR-dependent chloride efflux (Fig. 3).…”
Section: Discussionsupporting
confidence: 92%
“…We have shown previously that this assay is a sensitive measure of the phosphorylation of the CFTR R-R by the cAMP-dependent PKA (20). Roflumilast induced robust phosphorylation of isolated CFTR R-R in a dose-dependent fashion that was sensitive to the PKA inhibitor H89 ( Figure 3B).…”
Section: Roflumilast Activates Cftrdependent Anion Transport By Incrementioning
confidence: 70%
“…R-region phosphorylation was performed in COS7 cells as described (20). COS7 cells were transfected transiently with a plasmid encoding the CF R-region (amino acids 635-836) with an N-terminal HA epitope tag.…”
Section: Voltage Clamp Studies In Ussing Chambersmentioning
confidence: 99%
“…First-or second-passage primary human bronchial epithelial (HBE) cells were derived from lung explants (26,27). Cells were grown for 6-8 weeks until terminally differentiated.…”
Section: Dual Luciferase Assaymentioning
confidence: 99%
“…Short-circuit current (I sc ) was measured under voltage clamp conditions inUssing chambers (Physiologic Instruments, San Diego, CA) (21,26,27). Amiloride (100 mM) was added to block residual epithelial sodium channel current, followed by the CFTR agonist, forskolin, and the inhibitor, CFTR Inh -172 (10 mM).…”
Section: Short-circuit Current Measurementsmentioning
confidence: 99%